2006
DOI: 10.1111/j.0021-9029.2006.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetics: They Influence More Than Caucasian Female Facial Attractiveness

Abstract: The study explored whether 4 Caucasian women would be evaluated differently on 4 social measures depending on whether they were presented with or without makeup. ParticipantsF152 men and 171 womenFwere split into 2 groups and were presented with the women's facial photographs either with or without cosmetics. Women presented wearing cosmetics were perceived as healthier and more confident than when presented without. Participants also awarded women wearing makeup with a greater earning potential and with more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 16 publications
10
123
0
5
Order By: Relevance
“…Our results seem to show that a red lip color is sufficient enough to influence men's approach. These results are important given the fact that they again confirmed that makeup increases women's attractiveness (Graham & Jouhar, 1981;Cox & Glick, 1986;Cash, Dawson, Davis, Bowen, & Galumbeck, 1989;Workman & Johnson, 1991;Mulhern, Fieldman, Hussey, Lévêque, & Pineau, 2003;Nash, Fieldman, Hussey, Lévêque, & Pineau, 2006;Richetin, Huguet, & Croiset, 2007;Jacob, Guéguen, Boulbry, & Ardicioni, 2009), but they also showed that lipstick and the color of the lipstick can exert a single attractiveness effect. Indeed, in these previous studies, neither the color of the makeup nor the effect of lipstick alone were tested.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our results seem to show that a red lip color is sufficient enough to influence men's approach. These results are important given the fact that they again confirmed that makeup increases women's attractiveness (Graham & Jouhar, 1981;Cox & Glick, 1986;Cash, Dawson, Davis, Bowen, & Galumbeck, 1989;Workman & Johnson, 1991;Mulhern, Fieldman, Hussey, Lévêque, & Pineau, 2003;Nash, Fieldman, Hussey, Lévêque, & Pineau, 2006;Richetin, Huguet, & Croiset, 2007;Jacob, Guéguen, Boulbry, & Ardicioni, 2009), but they also showed that lipstick and the color of the lipstick can exert a single attractiveness effect. Indeed, in these previous studies, neither the color of the makeup nor the effect of lipstick alone were tested.…”
Section: Discussionmentioning
confidence: 71%
“…The literature examining the role of cosmetics in social perception has found that, overall, makeup is associated with a positive evaluation of a woman (Graham & Jouhar, 1981;Cash, Dawson, Davis, Bowen, & Galumbeck, 1989;Mulhern, Fieldman, Hussey, Lévêque, & Pineau, 2003;Nash, Fieldman, Hussey, Lévêque, & Pineau, 2006;Richetin, Huguet, & Croiset, 2007). Men's positive perceptions of the physical and sexual attractiveness of women wearing cosmetics were also observed.…”
Section: Introducationmentioning
confidence: 99%
“…That is, men and women may view women's cosmetics practices differently as a function of their own status acquisition mechanisms. Hence, while women with cosmetics are associated with higher status professions (Nash et al, 2006;Richetin et al, 2004), whether they are perceived as being high status through the perception of higher dominance or prestige is unknown, and whether this differs based on the perceivers' sex has yet to be explored.…”
Section: Methodsmentioning
confidence: 99%
“…Isto é devido, de acordo com Russell (2003), ao facto de que os cosméticos acentuam o dimorfismo sexual preexistente nas pessoas, tornando o rosto das mulheres mais feminino e logo mais atractivo. Considera-se ainda que a maquilhagem cosmética exerce mais do que uma simples influência na atractividade feminina; ela permite às mulheres parecerem mais saudáveis, mais confiantes e com um potencial mais elevado de obterem melhores salários com empregos mais prestigiados (Nash et al, 2006). Influenciando a heteropercepção, os cosméticos têm inevitavelmente um impacto no Self, uma vez que as avaliações de pessoas significantes influenciam a autopercepção de cada pessoa.…”
Section: Revisão De Literaturaunclassified
“…Esta relação, como afirmam Wicklund e Gollwitzer (1982), pode ser considerada como uma autocompletação simbólica do Self através da utilização dos cosméticos. O elevado envolvimento com estes produtos pode também ocorrer porque as pessoas compreendem que através da sua utilização a sua imagem corporal melhora (Mulhern et al, 2003;Osborn, 1996), tornando-se então mais atractivas e orientando-se para julgamentos mais favoráveis dos outros sobre si próprias (Nash et al, 2006). A nossa segunda hipótese mostra que, quanto maior for o envolvimento com os cosméticos, mais positivas são as atitudes em relação à sua publicidade (r=0,513).…”
Section: Modelo De Motivos De Compra De Cosméticosunclassified